(untitled) (Patan Pragya, 2021)
Human development should be seen as an extensive, innovative, appreciative and community procedure, rather than the simple expansion of health, education and income. The countries in this globe should have strong ‘human development policies and strategies to attained the better outcome in the sector of income, health and education. In this condition all state should focused to build basic human capabilities and should be related to attained peace, security and community participation for resource mobilization and for social dynamics. These necessities can be seen in a range of occurrence in past and present in different location. It is clear that low is the variation about the outcome of HDI with reference to time in a decade better are the strategies for the human development. In SAARC countries some examination of human development and its components were reviewed and use summary statistics found improved in the value of human development index. Similarly the scale of variations in different statistics are found in decreasing order. The value of coefficient of variances were 15.64% in 2014, 14.33% in 2018 and 13.8% in 2020 respectively. Those figures shows increasing in consistency in mean HDI with decreasing pattern in variation in value of HDI and progress in human development. The variation in these three components which is depending on strategies of the respective country. The peace, freedom with societal partnership, might be seen as a social democratic mission. The summary statistics reflect the situation of the variation in the SAARC countries. The variation in HDI is in decreasing order from 2014 to 2020. Similarly five countries are found below the average HDI out of eight countries and found in progress. Among these eight countries Sri Lanka is in top position where as Afghanistan is in the lowest position. These statistics clearly explored the existing scenario of the human development status of SAARC region.